Assessment of the Local Housing Policy of Łódź and Kraków in the Light of Selected Aspects - Parys, Artur Włodzimierz (Acta Universitatis Lodziensis. Folia Oeconomica, 2020)
The article carried out a study on the local housing policy of Łódź and Kraków in the year 2006 and 2017. A comparative analysis was carried out in terms of population, housing stock (including social and municipal flat), unemployment rate, income and expenditure of the budgets of the cities studied, the economic situation expressed in income budget per capita. The results of the quantitative analyzes carried out show the trend of decreasing the amount of housing stock in the examined cities. In recent years housing stock in Łódź have been decreasing more intensively than in Kraków, and the ownership structure of Łódź residential buildings is different from that of residential buildings in Krakow.